Customized e-communication map for landslide education project - Usuda, Yuichiro; Nakasu, Tadashi; Sakai, Naoki; Ahmad, Jamilah; Lateh, Habibah; Chua, Kok Hua (Japan International Cooperation Agency, 2014)
Providing disaster risk communication tools to improve the interface between local government and community through disaster education, decision-making and emergency response planning.